if x= 2^2/3+2^1/3, then prove that x^3-6x-6=0
Answers
Answered by
4
Answer:
Taking x= 2^(2/3) + 2^(1/3) we get
x = (cube root of 2)^2 + (cube root of 2)
[ Because power 1/3 is nothing but cube root]
Let's first find x^3,
x^3 = [ (cube root of 2)^2 + (cube root of 2) ]^3
Using (a+b)^3 formula we get
x^3 = 6 + 6[ 2^(2/3) + 2^(1/3) ]
Now let's find out 6x,
6x = 6( 2^(2/3) + 2^(1/3) )
Taking the equation x^3 - 6x -6 as A,
A = 6 + 6[ 2^(2/3) + 2^(1/3) ] - 6( 2^(2/3) + 2^(1/3) ) -6
Which gives A = 0.
Therefore x^3 - 6x - 6 = 0.
Hence proved.
Step-by-step explanation:
Please mark my answer as brainliest . Please
Similar questions